Do Financing and Investment Determine the Capital Market Reaction? Evidence from Listed Mining Companies in Indonesia - Surahman, Bambang; Khairani, Elisa; Erna, Erna; Erita, Erita (Universitas Syiah Kuala, 2020)
Objective The level of trust in the stocks market is one of the important factors to improve the companys image in facing the increasingly challenging global market. The stock markets trust can be analyzed by the business capital owned by its company. This research aims to analyze the influence of financing and investment on the dependent variables of capital reaction taking the samples of mining companies listed on the Indonesia Stock Exchange (IDX). This study also analyzes the responses in the ability of mining companies in the capital market. Design/methodology The associative approach has been used in this research and a descriptive research model has been utilized. This research is intended to examine the free effect of financing and investment on the dependent variable of the market reaction. The sample used in this study is saturated sampling. Samples of 32 companies out of 44 mining companies listed on the IDX were drawn for analysis purposes.Results This study found that DER financing and PER investment (price-earnings ratio) have no significant impact on capital market reaction TVA (trading volume activity) in listed mining companies in Indonesia. It can be concluded that increasing quality of mining companies in Indonesia are mostly not influenced by the power of DER and investment PER.